The Development of the Anglo-Muhammadan Law in India - Borroni, Andrea; Seghesio, Marco (Journal of Malaysian and Comparative Law, 2014)
The Anglo-Muhammadan Law represents a peculiarity within the current context of comparative law, owing to its threefold nature of Muslim personal law, influenced by the Common Law, and belonging to the broader Indian legal system. Nonetheless, despite its singularity, it represents a field of study which is frequently overlooked. The present essay attempts, at least to some extent, to shed light upon it. In the first place, the article provides an historical overview of the development of the Anglo-Muhammadan Law, focusing on the main transformations and innovations introduced by the British and their unavoidable legal, social and religious consequences. This essay, however, illustrates, in addition, that, despite a powerful drive towards uniformity fostered by the prevailing system, the Anglo-Muhammadan Law preserves the distinctive features of the community it governs, for identity reason. Hence, the peculiar outcomes of the evolution of this branch of law could serve as a model to other national legislators facing similar issues within multicultural and multi-ethnic contexts.